BET inhibitor and CDK4/6 inhibitor synergistically inhibit breast cancer by suppressing BRD4 stability and DNA damage repair - Shuaishuai Chi; Fan Wei; Yangsha Li; Lei Yu; Chuyao Ma; Yanfen Fang; Biyu Yang; Yi Chen; Jian Ding (Translational Oncology, 2025)
CDK4/6 inhibitors have shown clinical benefits in hormone receptor positive breast cancer. However, monotonous indications and unclear resistance mechanisms greatly limit the clinical application of these inhibitors. We attempt to improve the therapeutic effect of CDK4/6 inhibitors against breast cancer by combination with BET inhibitors. Although this combination therapy has begun to be studied in recent clinical trials, the mechanism of action is not clear. We provide the evidence that CDK4/6 inhibitor LY2835219 plus BRD4 inhibitor OTX-015 synergistically inhibits both ER positive and triple-negative breast cancer cells growth in vitro and in vivo. Mechanistically, LY2835219 accelerates the degradation of BRD4 through the proteasome pathway via inhibition of CDK4 activity. This instability of BRD4 protein in turn enhances the anti-tumor effect of CDK4/6 inhibitor by suppressing transcription of DNA damage repair gene RAD51, and synergistically promotes γ-H2AX accumulation and DNA double-strand breaks. Overall, we demonstrated the potential combined therapeutic value of CDK4/6 and BRD4 inhibitors and elucidated the mechanisms, which may provide a new rational approach for breast cancer patients.